SLOPE STABILITY ANALYSIS USING FINITE ELEMENT METHOD (FEM) IN WARA OPEN PIT COAL MINE, PT ADARO INDONESIA, TABALONG, SOUTH KALIMANTAN - Sihotang, Josua Washington; Bakhtiar, Taufiq; Khoirullah, Nur; Sophian, Raden Irvan; Zakaria, Zufialdi (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
The stability of slope is impacted by Rock Mass Rating, material properties, and slope geometry. Furthermore, the slope stability analysis was needed to know the slope stability condition. This research aims to know the Strength Reduction Factor (SRF) value by using Finite Element Method (FEM) using Hu=1 and Hu=Auto. The geotechnical mapping that is Rock Mass Rating (RMR) and Measured Section were done to get the Geological Strength Index (GSI) and profile of layer rocks in highwall slope SCT_J1 and SCT_J2. From the FEM analysis, actual slope SCT_J1 has the SRF=1.25 with Hu=1 and SRF=1.4 with Hu=Auto. SCT_J2 has SRF=1.21 with Hu=1 and SRF=1.3 with Hu=Auto. From the slope stability analysis, SCT_J1 and SCT_J2 were classified into stable slope due to the SRF value higher than 1.2.